2011
DOI: 10.1021/jf2018935
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phytochemicals of Leaf Essential Oils of Cinnamomum osmophloeum Prevent Lipopolysaccharide/d-Galactosamine (LPS/d-GalN)-Induced Acute Hepatitis in Mice

Abstract: The purpose of this study was to investigate the bioactive phytochemicals of leaf essential oils of Cinnamomum osmophloeum on lipopolysaccharide/D-galactosamine (LPS/D-GalN)-induced acute hepatitis. The results revealed that post-treatment with 100 μmol/kg trans-cinnamaldehyde, (-)-aromadendrene, T-cadinol, or α-cadinol significantly decreased the aspartate aminotransferase (AST), alanine aminotransferase (ALT), tumor necrosis factor-α (TNF-α), and interleukin 6 (IL-6) levels in serum. Moreover, both T-cadinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 23 publications
1
25
1
2
Order By: Relevance
“…Humulene has been reported to produce anti-inflammatory effect and also has inhibitory effect on tumor necrosis factor- α -/(TNF- α ) and interleukin-1 β (IL1B) [ 30 ]. α -Cadinol is an antifungal [ 31 ] and hepatoprotective [ 32 ]. C 14 H 14 O is arachidic acid, a saturated fatty acid [ 33 ], C 20 H 40 O 2 is phytanic acid, a branched fatty acid, and its metabolites have been reported to bind or activate transcription factors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humulene has been reported to produce anti-inflammatory effect and also has inhibitory effect on tumor necrosis factor- α -/(TNF- α ) and interleukin-1 β (IL1B) [ 30 ]. α -Cadinol is an antifungal [ 31 ] and hepatoprotective [ 32 ]. C 14 H 14 O is arachidic acid, a saturated fatty acid [ 33 ], C 20 H 40 O 2 is phytanic acid, a branched fatty acid, and its metabolites have been reported to bind or activate transcription factors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Terpinenes: Borneol; camphene; camphor; limonene; linalool; myrcene; p-cymene; spathulenol; viridiflorol; b-caryophyllene; b-pinene; d-cadinene; ⍺-cadinol; ⍺pinene; ⍺-terpineol [176] [209] Kaempferol glycosides: [210] Anticancer, [130,211] antidiabetic, [212,213] antidyslipidaemic, [214] antiinflammatory, [209,215] antimicrobial [216,217] , antioxidant, [213,218] cardioprotective, [219] cytotoxicity, [220] hair growth, [221] hepatoprotective, [222] hypolipidaemic effect, [223] hypouricaemic effects, [224] immunomodulatory, [225] larvicidal, [29] pancreas-protective effect, [226] tyrosinase, [220,227] wound healing, [227] xanthine oxidase inhibitory [224] Arthritis, [228] cough and cold, [228] diabetes, [228] infection, [222] inflammation, [228] nerve pains, [228] pyrexia [228] Bark Flavonoids: (E)-Cinnamaldehyde; (Z)cinnamaldehyde. [229] Hydrocarbon: Phenol; c-muurolene [229] Flavonoids: cis-Cinnamaldehyde; transcinnamaldehyde [5,230,231] ; cinnamaldehyde.…”
Section: Leavesmentioning
confidence: 99%
“…Among them include 9, 12-Octadecadienoic acid (Z, Z)-, methyl ester, a fatty acid methyl ester detected in M. capensis methanol extract has been showed to exhibit antibacterial activity [13]. α-cadinol a sesquiterpene found in the extract of the understudy plant reported to possess antifungal and as hepatoprotective agents [14,15].…”
Section: Resultsmentioning
confidence: 99%